A Pilot Scale Study of Greywater Treatment Using Gravel Sand Followed by Granular Activated Carbon - Samal, Milan; Lama, Shreeja Lopchan; Luitel, Subodh; Ghimire, Anish (Kathmandu University Journal of Science Engineering and Technology, 2020)
Greywater (GW) reuse can help reduce water footprint if used as an alternative source of water for non-potable use, but it requires careful treatment to remove the contaminants. Therefore, the objective of this study was to develop a simple treatment system with low-cost and low footprint. This study evaluated the performance of a treatment plant with flow rate of 1 m3/day and organic loading rate of 0.32 kg COD/m3.day for on-site treatment and reuse of water collected from wash basins and sinks, as a major source of GW. Gravel sand filter followed by granular activated carbon (GAC) were used as filter medias. Results showed that the removal efficiencies of TSS, COD and BOD concentration were reduced by an average of 53%, 57% and 47% respectively corresponding to 36 mg/L, 125.6 mg/L and 85.3 mg/L, respectively in the treated effluent. The treated effluent satisfied Nepal Water Quality Guideline for irrigation for parameters like EC, pH and TSS. However, the microbial removal efficiency was found to be low so, use of disinfectant is recommended. The cost-benefit analysis indicated payback after 500 m3 of GW treatment and reuse, thereby reducing water demand with monetary benefits.